Validating the growth increment periodicity in the otoliths of three small progenetic gobies - Sílvia Pérez-Mayol (Scientia Marina, 2021)
We determined the efficacy of marking the otoliths of three small-sized progenetic gobies to validate their increment periodicity. These small gobies have high mortalities and rearing difficulties, making direct validation difficult. The otoliths were marked by immersing the fish in a bath of alizarin red S. The fishes were euthanatized and the number of increments in their otoliths laid down after the fluorescent mark were counted and compared with the number of elapsed days. The results validated the daily periodicity of Aphia minuta and Pseudaphya ferreri. The high mortality hindered the validation of Crystallogobius linearis.